THE ROLE OF SOCIAL COMMERCE CONSTRUCTS, SOCIAL SUPPORT, AND TRUST IN COMMUNITY ON SOCIAL COMMERCE ACTIVITIES - Hidayatulloh, Amir (Muhammadiyah International Journal of Economics and Business, 2018)
This study  aims  to  analyze  social  commerce  constructs, social  support,  and  individual  trust in the  community   in   social   commerce   activities.   Social   support   includes   emotional   support  and informational  support.  The population  was  social  media  users, while  the  samples were  social media users who had made purchase at least two transactions through social media. The sampling technique was convenience sampling. Totally, 162 respondents were involved. Hypothesis testing was  done using  Warp PLS. This study  reveals that individual  trust in  the community  can be built directly  through  the social  commerce  constructs. These  constructs affects both  emotional  support and information support, in which they will ultimately affect the individual trust in the community. Furthermore,  social  commerce  intention  is influenced  by  individual  trust in  the community  and emotional  support.  However,  information  support does not  affect  the social commerce  intention.